2013
DOI: 10.3109/13813455.2013.789529
|View full text |Cite
|
Sign up to set email alerts
|

A combination of two electrophoretical approaches for detailed proteome-based characterization of SCLC subtypes

Abstract: Additional CTAB-SDS page is a complementary method to IEF-SDS page revealing a complete new subset of proteins differentially expressed between GLC1 and GLC1 M13 cells SCLC subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…To cope with winter or cold conditions, small mammals always enhance nonshivering thermogenesis (NST), and the major site of its occurrence is brown adipose tissue (BAT). Long-term cold exposure also leads to "browning" in white adipose tissue (WAT), which produces BAT-like properties (Peschechera & Eckel 2013), and transcriptional activation of many genes involved in lipid catabolism (Christian 2005;Kim et al 2017). In the past, mammalian adipose tissues were mainly divided into WAT and BAT, but in recent years another adipose tissue was found, which is induced from WAT, called "beige adipose tissue" (Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To cope with winter or cold conditions, small mammals always enhance nonshivering thermogenesis (NST), and the major site of its occurrence is brown adipose tissue (BAT). Long-term cold exposure also leads to "browning" in white adipose tissue (WAT), which produces BAT-like properties (Peschechera & Eckel 2013), and transcriptional activation of many genes involved in lipid catabolism (Christian 2005;Kim et al 2017). In the past, mammalian adipose tissues were mainly divided into WAT and BAT, but in recent years another adipose tissue was found, which is induced from WAT, called "beige adipose tissue" (Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, HL-60 cells treated with 1.25 mg/l DADS for 12 h exhibited an increase in DJ-1 expression in cytoplasm and decreased expression in the nucleus when compared with cells treated with 1.25 mg/l DADS for 8 h. These results suggest that DJ-1 protein may be translocated back from the cell nucleus into the cytoplasm following 8 h of DADS exposure. Immunocytochemistry and immunofluorescence assay analysis results confirmed the observed translocation of DJ-1 from the cytoplasm to the nucleus following exposure to DADS for 8 h. Proteins are often distributed in different subcellular locations, which is associated with their different functions (27). A previous study demonstrated that the DJ-1 protein, which is considered to be involved in the regulation of gene transcription, translocates from the cytoplasm to the nucleus during S phase of the cell cycle upon mitogen stimulation (28).…”
Section: Discussionmentioning
confidence: 56%
“…For enrichment analysis, p-values were corrected according to Benjamini Hochberg if appropriate and a list of proteins identified from a comparison of small cell lung cancer cell lines [25] was used as background list to exclude a bias introduced by the 2D-gel based method favoring higher abundant and non-membranous proteins.…”
Section: Protein Identification By Mass Spectrometrymentioning
confidence: 99%